Rasionalitas Beragama Pekerja Seks Komersial (PSK) - Rahmi Putri; Syafruddin Syafruddin (Indonesian Center for Religion and Society Studies (InTReSt), 2020)
This paper aims to explore religious rationality among prostitutes. This study is a case study with a qualitative descriptive method at the Panti Sosial Karya Wanita Andam Dewi Solok. Data was collected using in-depth interview techniques. Using Max Weber's rationality theory as an analytical tool, this study found several important findings. First, the choice to enter the world of prostitution is a rational action taken by prostitutes. The act of prostitution that is carried out is an action that is goal-oriented (instrumentally rational). Actions of prostitution are rationally strived to gain utility, either to show